Acceleration of Telemedicine Use for Chronic Neurological Disease Patients during COVID-19 Pandemic in Yogyakarta, Indonesia: A Case Series Study - Pinzon, Rizaldy; Paramitha, Dessy; Wijaya, Vincent Ongko (Kesmas, 2020)
COVID-19 preventions have cut access to routine medical care, especially for many chronic neurological disease patients. This condition has especially promoted telemedicine use in providing healthcare. This study aimed to review telemedicine use catalyzed by several regulations of the Indonesian Government and review 20 cases from Bethesda Hospital in Yogyakarta providing online consultation services. Perceptions of experience on telemedicine were collected from neurological patients at the hospital who were asked about their impressions of consultations and pharmacy medication services, and their suggestions about the new system in outpatient consultations. The regulations for telemedicine use are relevant because of these patients’ risks related to comorbidities and treatments. Of the 20 respondents involved in this study, 15 (75%) were satisfied with the service, 3 (15%) very satisfied, and 2 (10%) others neutral. Most respondents suggest improvement of reimbursement (80%) and others suggest improvement on medications (10%) and services (10%). System and hospital requirements for telemedicine services for neurological cases have been accelerated due to the pandemic. Telemedicine is a way to provide healthcare needed by patients at high risks for COVID-19 fatality related to comorbidities and treatments. Payment regulations, regulatory structures, state licensing, and credentialing across hospitals for better telemedicine experience need to be enhanced.